Deconstructing the Decline in Inequality in Latin America - Lustig, Nora; Lopez-Calva, Luis F.; Ortiz-Juarez, Eduardo (World Bank, Washington, D.C, 2013)
Inequality in Latin America unambiguously declined in the 2000s. The Gini coefficient fell in 16 of the 17 countries where there are comparable data, and the change was statistically significant for all of them. Existing studies point to two main explanations for the decline in inequality: a reduction in hourly labor income inequality, and more robust and progressive government transfers. Available evidence suggests that it is the skill premium -- or, more precisely, the returns to primary, secondary, and tertiary education vs. no schooling or incomplete primary schooling -- that drives the decline in hourly labor income inequality. The causes behind the decline in returns to schooling, however, have not been unambiguously established. Some studies find that returns fell because of an increase in the supply of workers with more educational attainment; others, because of a shift in demand away from skilled labor.